Conversion of LDPE Plastic Oil to Gasoline by Supercritical Water Liquefaction - Elyana, Enggar Ira; Febriyanti, Febriyanti; Rohim, Fathur; Rusdy, Rafael Arthorito; Sari, Diva Luckyta; Juwono, Hendro (Jurnal ILMU DASAR, 2024)
LDPE (Low Density Polyethylene) is one of the plastic waste that is often found in the surrounding environment. Based on data from the National Waste Management Information System (SIPSN) in 2022, waste in Indonesia reached 17.834.071 tons/year with 18.5% being plastic waste. Plastic waste management generally uses recycling. However, recycling plastic waste is not efficient enough in tackling plastic waste in Indonesia. Recently, a promising alternative recycling method for the future is pyrolysis, a process to convert plastic into fuel oil. However, the pyrolyzed oil still contains impurities that reduce the quality of the oil. As an effort to improve the quality of pyrolysis oil, the author proposes the addition of zeolite catalyst in the pyrolysis process followed by the Supercritical Water Liquefaction (SWL) method. The zeolite catalyst aids the degradation process thereby accelerating the reaction rate. The SWL method is able to convert plastic waste into low molecular weight chemicals. The results obtained will be analyzed by gas chromatography mass spectroscopy (GC-MS) to determine the length of the carbon chain in the sample. Based on the chromatography data, it is found that the number of peaks and retention times show carbon chains ranging from C8-C12, from these results it can be identified that the sample is included in kerosene or kerosene compounds. After the SWL process, the percentage of kerosene and diesel is reduced to 11% gasoline. So the Supercritical Water Liquefaction process is proven to break down long hydrocarbon chains into lighter ones.